TATA KELOLA BUMDES BERBASIS PRINSIP GOOD CORPORATE GOVERNANCE DI DESA MENGKOPOT KECAMATAN TASIK PUTRI PUYU KABUPATEN KEPULAUAN MERANTI TAHUN 2019-2024 - ,, Syafri; Rafi, M. (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2025)
This research is motivated by the phenomenon related to BUMDes "Usaha Bersama" Mengkopot Village, which has implemented various business programs, attracting the attention of this research because after six years of establishment, this BUMDes is still in the growing category. The main problem in this study is the inability and professionalism of the managers and low creativity. This study aims to look at the governance of BUMDes in Mengkopot Village using the theory of Good Corporate Governance principles by the Komite Nasional Kebijakan Governance (KNKG). This study aims to describe the phenomenon systematically and accurately using qualitative descriptive methods, including interviews, documentation, and recording and recording data. The results of this study indicate that the implementation of the principles of Good Corporate Governance in BUMDes "Usaha Bersama" Mengkopot Village is still not optimal, with minimal transparency principles, weak accountability principles, less than optimal responsibility principles, independence principles that are still a challenge, and principles of equality and fairness that need to be improved so that management is fairer and more sustainable. So, the conclusion is that the implementation of the Good Corporate Governance principle in BUMDes “Usaha Bersama” Mengkopot Village is still weak. Transparency, accountability, and strengthening of the business are needed to be more professional, sustainable, and beneficial to the community. Keywords: Governance, BUMDes, Good Corporate Governance